IMPROVING STUDENTS WRITING SKILL IN NARRATIVE TEXT BY USING DISPERSION IMAGINATION - Herlin Apriliyani; Fadilla Oktaviana; Ida Nuraida (Journal of English Language Teaching and Literature (JELTL), 2019)
The objective of the study were (1) To know the process of teaching writing skill in narrative text at tenth grade of SMK PGRI 3 Kota Serang (2) To find out the result of students writing skill in narrative text by using dispersion imagination at tenth grade of SMK PGRI 3 Kota Serang. This research is used a mixed method research design, classroom action research. The result of the research were (1) the process of teaching narrative text using dispersion imagination in writing skills of two steps; pre-cycle and cycle. The result of research showed that the research in cycle 1, the writer used the move picture, the students to listen and look at the move picture in slide at the Power Point about the material. The students write narrative text from the story by using dispersion imagination. In cycle 2, the use of film is able to improve students writing skill in narrative text and develop idea to write well. While the role of teachers who are not just as facilitators, but also as a motivator and inspirator are also able to provide new supported in the learning process. There is improvement in writing skill of the students after the treatment. It can be seen from their main score of pre-test and post-test. (2) There was improvement in the pre-test main score (41.00), the first post-test mean score (45.00), and the second post-test main score (76.00). The achievement of writing in post-test is 76,00%. In conclusion, there was significant improvement of the students in writing skill in narrative text by using dispersion imagination.